Contemporary Sundanese Quran; A departure or divine proximity? - Hanafi, Taufiq (UI Scholars Hub, 2025)
The Sundanese are deeply immersed in Islam, as exemplified by the adage, “to be Sunda is to be Muslim”. An important initiative within this cultural-religious context is the translation of the Quran into low vernacular Sundanese, departing from the formal and codified language forms of the original. Despite concerns about potential textual transgression, this translation negotiates linguistic barriers and reinforces cultural identity within the Islamic framework. This paper examines the contemporary Sundanese translation of the Quran, Ayat Suci Lenyepaneun (1989), and argues that its use of low colloquial Sundanese not only enhances the Quran’s legibility but also establishes an immediate connection between readers and their faith.